Inhaltanalyse der Nachrichten über die Deutsche Sprache in Türkischen Zeitungen. - ARSLAN ÇAVUŞOĞLU, Ayşe (Itobiad: Journal of the Human & Social Science Researches / İnsan ve Toplum Bilimleri Araştırmaları Dergisi)
This study aims to examine the news published in Turkish newspapers between 2017 and 2021, focusing on the German language (German news stories). The interest in this topic stems from the significance of Turkish-German relations and the portrayal of the German language in the media. Initially, ten Turkish newspapers were selected using purposeful sampling procedures to conduct the investigation. After an elimination process, seven newspapers remained for the analysis. The electronic archives of these newspapers were utilized for data collection, with the keyword "German or German language" being employed. The collected data were analysed using content analysis techniques to comprehensively examine the news content. Four main variables were considered during the analysis of newspaper articles: circulation over the years regarding the German language, newspaper sections where the news was published, the approach taken in the news reports (positive, negative, neutral), and the content of the news itself. The results of this study indicate that the number of news articles concerning the German language in Turkish newspapers has increased over the years. This suggests an elevated interest in the German language within Turkish society and emphasizes the significant role played by the media in reporting on this topic. The findings of this study contribute to expanding understanding of the perception and portrayal of the German language in the Turkish press. Additionally, they provide a foundation for further investigations into Turkish-German relations and the influencing factors on media coverage.